1991
DOI: 10.1002/jez.1402600309
|View full text |Cite
|
Sign up to set email alerts
|

The behavior and cytoskeletal system of chick gastrula mesodermal cells on substrata coated with lines of fibronectin

Abstract: In order to investigate the mechanism of the formation of the mesodermal layer during chick gastrulation, we observed the behavior of fragments of mesodermal cells explanted and cultured on substrata coated with parallel lines of fibronectin (FN). We also examined the distribution of F-actin, alpha-actinin, and vinculin in explanted fragments by immunocytochemical methods noting particularly their distribution with respect to FN lines. Explants of mesodermal cells flattened on FN-coated substrata and then beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…5B). These stresses pull precardiac mesoderm through the veins toward the caudal end of the heart, possibly inducing additional influx of cells through active migration along lines of stress-aligned fibronectin (Linask and Lash, 1986;Linask and Lash, 1988a;Linask and Lash, 1988b;Toyoizumi et al, 1991;Trinh and Stainier, 2004).…”
Section: Integrated Hypothesis For C-loopingmentioning
confidence: 99%
“…5B). These stresses pull precardiac mesoderm through the veins toward the caudal end of the heart, possibly inducing additional influx of cells through active migration along lines of stress-aligned fibronectin (Linask and Lash, 1986;Linask and Lash, 1988a;Linask and Lash, 1988b;Toyoizumi et al, 1991;Trinh and Stainier, 2004).…”
Section: Integrated Hypothesis For C-loopingmentioning
confidence: 99%
“…Highly conserved cytoskeletal proteins such as tubulin (α and β‐5 chain), actin (cytoplasmic and alpha‐skeletal), desmin, adseverin (Ads), and α‐actinin‐3 (actin binding protein) were upregulated in placental tissues during early and mid gestation. In early gestation, this upregulation is related to amniote morphogenetic rearrangements when the zygote is under cleavage and cellular differentiation, for example, upregulation in chicken (Toyoizumi et al., ) and mammalian (Sparn et al., ) gastrulation, principally in reptiles where a bi‐modal strategy of gastrulation (involution and ingression) has been suggested (Stower et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that cells can move passively as a result of their attachment to actively migrating cells. In explants of cultured chick embryo gastrula mesoderm motile activity appears to be confined to a subgroup of cells with stress fibers that pull cells, without stress fibers, passively along [Toyoizumi et al, 1991]. During morphogenesis and wound healing, migrating mesenchymal and epidermal cell sheets also appear to contain both actively and passively migrating cells [Trinkaus, 1976[Trinkaus, , 1982.…”
Section: Discussionmentioning
confidence: 99%